Measles in Vaccinated People: Epidemiology and Challenges in Surveillance and Diagnosis in the Post-Elimination Phase. Spain, 2014–2020 - Noemí López-Perea; Aurora Fernández-García; Juan Emilio Echevarría; Fernando de Ory; Mayte Pérez-Olmeda; Josefa Masa-Calles (Viruses, 2021)
The MMR vaccination program was introduced in Spain in 1981. Consistently high vaccination coverage has led to Spain being declared free of endemic measles transmission since 2014. A few imported and import-related cases were reported during the post-elimination phase (2014 to 2020), with very low incidence: three cases per million of inhabitants a year, 70% in adults. In the post-elimination phase an increasing proportion of measles appeared in two-dose vaccinated individuals (up to 14%), posing a challenge to surveillance and laboratory investigations. Severity and clinical presentation were milder among the vaccinated. The IgM response varied and the viral load decreased, making the virus more difficult to detect. A valid set of samples (serum, urine and throat swab) is strongly recommended for accurate case classification. One third of measles in fully vaccinated people was contracted in healthcare settings, mainly in doctors and nurses, consistent with the important role of high intensity exposure in measles breakthrough cases. Surveillance protocols and laboratory algorithms should be adapted in advanced elimination settings. Reinforcing the immunity of people working in high exposure environments, such as healthcare settings, and implementing additional infection control measures, such as masking and social distancing, are becoming crucial for the global aim of measles eradication.